Passage‐dependent cancerous transformation of human mesenchymal stem cells under carcinogenic hypoxia. Issue 7 (8th April 2013) - Crowder, Spencer W.; Horton, Linda W.; Lee, Sue Hyun; McClain, Colt M.; Hawkins, Oriana E.; Palmer, Amanda M.; Bae, Hojae; Richmond, Ann; Sung, Hak‐Joon
Abstract : Bone marrow‐derived human mesenchymal stem cells (hMSCs) either promote or inhibit cancer progression, depending on factors that heretofore have been undefined. Here we have utilized extreme hypoxia (0.5% O2 ) and concurrent treatment with metal carcinogen (nickel) to evaluate the passage‐dependent response of hMSCs toward cancerous transformation. Effects of hypoxia and nickel treatment on hMSC proliferation, apoptosis, gene and protein expression, replicative senescence, reactive oxygen species (ROS), redox mechanisms, and in vivo tumor growth were analyzed. The behavior of late passage hMSCs in a carcinogenic hypoxia environment follows a profile similar to that of transformed cancer cells ( i.e., increased expression of oncogenic proteins, decreased expression of tumor suppressor protein, increased proliferation, decreased apoptosis, and aberrant redox mechanisms), but this effect was not observed in earlier passage control cells. These events resulted in accumulated intracellular ROS in vitro and excessive proliferation in vivo . We suggest a mechanism by which carcinogenic hypoxia modulates the activity of three critical transcription factors (c‐MYC, p53, and HIF1), resulting in accumulated ROS and causing hMSCs to undergo cancer‐like behavioral changes. This is the first study to utilize carcinogenic hypoxia as an environmentally relevant experimental model for studying the age‐dependent cancerous transformation of hMSCs.— Crowder, S. W., Horton, L. W., Lee, H. H., McClain, C. M., Hawkins, O. E., Palmer, A. M. Bae, H., Richmond, A., Sung, H.‐J. Passage‐dependent cancerous transformation of human mesenchymal stem cells under carcinogenic hypoxia. FASEB J. 27, 2788‐2798 (2013). www.fasebj.org